Effects of Collaborative Strategic Reading (CSR) on EFL Learners’ Reading Comprehension, Reading Motivation, and Metacognitive Awareness - Sarshogh, Maryam; Rezvani, Ehsan; Karimi, Fatemeh (Innovare Journal of Education, 2024)
This study focused on investigating the effects of collaborative strategic reading (CSR) on English as a foreign language (EFL) learners’ reading comprehension, second language (L2) reading motivation, and metacognitive awareness. Following a quasi-experimental design, 48 Iranian EFL learners were selected from four intact language institute classes. Two of these classes were considered experimental groups (EGs), and two were regarded as control groups (CGs). Then, all four classes received the three pretests of the study (Reading Comprehension pretest, L2 Reading Motivation questionnaire, and metacognitive awareness questionnaire). Next, the treatment phase of the study began and all the groups received reading comprehension instruction. In the EGs, the teacher conducted the essential elements of cooperative learning through CSR strategies (preview, click & clunk, get the gist, and wrap up). On the other hand, CG learners received traditional reading comprehension classes with no group work. After the treatment, all four groups received the three posttests. The results of three one-way ANCOVAs revealed that CSR was significantly more effective than traditional instruction in improving EFL learners’ reading comprehension. In addition, it was found that CSR was significantly effective in improving EFL learners’ reading motivation and metacognitive awareness. The findings of the study can be utilized by language practitioners, materials, and curriculum developers to consider EFL students’ needs and goals in L2 reading.